THE ANTIOXIDANT EFFECTS OF CAPPARIS OVATA AND DEFERASIROX IN PATIENTS WITH THALASSEMIA MAJOR - Duran Canatan; Handan Duman; Guchan Emine Alanoglu; Recep Sutcu; Tufan Nayır (Mediterranean Journal of Hematology and Infectious Diseases)
Iron overload and auto-oxidation of unpaired globin chains are  the main causes of oxidative stress in patients with thalassemia major. In the present study, we aimed to investigate the antioxidant effects of capparis ovatta and deferasirox in thalassemic patients.